MiR‐200a enhances TRAIL‐induced apoptosis in gastric cancer cells by targeting A20. (25th January 2018) - Guo, Tianshu; Zhang, Ye; Qu, Xiujuan; Che, Xiaofang; Li, Ce; Fan, Yibo; Wan, Xing; Ma, Rui; Hou, Kezuo; Zhou, Huiming; He, Xiaowei; Hu, Xuejun; et al.
Abstract: Tumor necrosis factor‐alpha‐related apoptosis‐inducing ligand (TRAIL) triggers apoptosis by inducing the death‐inducing signaling complex (DISC) formation. Recently, TNFα‐induced protein 3 (TNFAIP3, A20) was reported to prevent TRAIL‐induced caspase 8 cleavage in the DISC by mediating ubiquitination of RIP1 in glioblastoma. However, whether A20 regulates caspase 8 cleavage in the DISC when TRAIL induces apoptosis in gastric cancer cells is unknown. In the present study, A20 interacted with RIP1 and DR4 in MGC803 and SGC7901 gastric cancer cells. Treatment with TRAIL promoted the A20‐mediated polyubiquitination of RIP1, caspase 8 translocation into the DISC, and the interaction between caspase 8 and ubiquitinated RIP1. Inhibition of A20 expression prevented the polyubiquitination of RIP1 and promoted caspase 8 cleavage. Moreover, our data clarified that A20 is a target of miR‐200a. Overexpression of miR‐200a inhibited A20 expression and polyubiquitination of RIP1 and then promoted cleavage of caspase 8 and TRAIL‐triggered apoptosis. Taken together, our results indicate that miR‐200a enhanced TRAIL‐triggered apoptosis in gastric cancer cells by targeting A20.